The Influence of Financial Accounting Standards, Accounting Information Systems, and Internal Control Affect Financial Statement Quality in Micro, Small, and Middle Enterprises in Garut Regency - Alfhalares, Dede Rifky; Muchtar, Muhammad Ihsan (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2024)
This study explores the impact of Financial Accounting Standards, Accounting Information Systems, and Internal Control on the quality of financial statements in Micro, Small, and Middle Enterprises (MSMEs) in Garut Regency, Indonesia. It employs a quantitative methodology, gathering data from 100 randomly selected MSMEs and analyzing it using multiple regression and correlation techniques to assess how these factors influence financial reporting quality. The findings reveal that these components significantly enhance financial statement quality, thereby potentially increasing MSMEs' access to financial services and supporting sustainable growth. The study emphasizes the need for policy interventions to improve financial literacy and the adoption of standardized accounting practices, alongside integrating advanced technologies into financial management processes. This research provides valuable insights for policymakers and educational institutions to develop targeted programs that enhance economic stability and growth in MSME-rich regions like Garut Regency and beyond.